Avaliação da formação de biofilme sobre resina odontológica irradiada com 403 NM contendo nanopartículas de prata - Moraes, Alexandre Bergamo (2020)
The acrylic resin used in the construction of oral prostheses is highly colonized by Candida albicans. The difficulty in hygiene, especially of the prostheses type protocol bolted on implants, favors the emergence of oral candidiasis. This study evaluated the in vitro antifungal effect of incorporation of nanoparticles of silver (AgNPs) in samples of acrylic resin of methyl methacrylate irradiated by LED light and also the mechanical properties of this new material. The AgNPs were synthesized by the reduction of silver nitrate and sodium boroidreto in aqueous solution. The samples impregnated with the AgNPs, were obtained by means of cylindrical metal matrices in the dimensions of 12 mm in diameter by 3 mm in height. The solution containing the AgNPs was added to the liquid component of acrylic resin in concentrations of 0% as control, 2%, 4% and 8%, based on the mass of the polymer resin. This mixture was included in silicone molds and pressed in muffle. The samples were infected with strains of Candida albicans and the group with 8% was irradiated with a LED light source of 403nm at three different times, 60, 180 and 300 seconds, to evaluate its effect on the AgNPs. Mechanical tests of elasticity were also performed. Conclusion: With the concentrations of AgNPs used, there were no changes in any of the antifungal groups, even those where the samples were treated with the LED light. Mechanically, the group impregnated with 2% of AgNPs showed a slight increase in the Modulus of elasticity.